The function f(x) = `e^(3x^2)`

f'(x) = `e^(3x^2)*6x`

f''(x) = `e^(3x^2)*6x*6x + e^(3x^2)*6`

=> `36x^2*e^(3x^2) + 6*(e^(3x^2))`

=> `(36x^2 + 6)*e^(3x^2)`

f'''(x) = `(36x^2 + 6)*e^(3x^2)*6x + 72x*e^(3x^2)`

=> `e^(3x^2)*(216x^3 + 108x)`

`f'(x) - f''(x) - f'''(x)`

=> `e^(3x^2)*6x - (36x^2 + 6)*e^(3x^2) - (e^(3x^2)*(216x^3 + 108x)`

=> `e^(3x^2)*(6x -...

## View

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The function f(x) = `e^(3x^2)`

f'(x) = `e^(3x^2)*6x`

f''(x) = `e^(3x^2)*6x*6x + e^(3x^2)*6`

=> `36x^2*e^(3x^2) + 6*(e^(3x^2))`

=> `(36x^2 + 6)*e^(3x^2)`

f'''(x) = `(36x^2 + 6)*e^(3x^2)*6x + 72x*e^(3x^2)`

=> `e^(3x^2)*(216x^3 + 108x)`

`f'(x) - f''(x) - f'''(x)`

=> `e^(3x^2)*6x - (36x^2 + 6)*e^(3x^2) - (e^(3x^2)*(216x^3 + 108x)`

=> `e^(3x^2)*(6x - 36x^2 - 6 - 216x^3 - 108x)`

=> `e^(3x^2)*(-216x^3 - 36x^2 - 102x - 6)`

**The expression for `f'(x) - f''(x) - f'''(x) = e^(3x^2)*(-216x^3 - 36x^2 - 102x - 6)` **